Raising of the participation age in the UK: the dichotomy between full participation and institutional accountability. (2015) - Lambert, Steve; Maylor, Uvanney; Coughlin, Annika
At a time of mass youth unemployment in the UK, the introduction of the Raising of the Participation Age (RPA) policy advocates the benefits of a prolonged period of education for all young people. As part of the policy, accountability was placed on schools for its implementation, with government imposed destination measures being used as an indicator of the policy's success. This paper argues that RPA will have little impact on young people who are Not in Education, Employment and/or Training (NEET) and that the accountability for the policy's implementation is at best problematic and at worse fundamentally flawed.